2023
DOI: 10.1002/aur.2901
|View full text |Cite
|
Sign up to set email alerts
|

Visual processing in genetic conditions linked to autism: A behavioral study of binocular rivalry in individuals with 16p11.2 deletions and age‐matched controls

Abstract: Close phenotypic characterization of individuals with genetic conditions linked to autism provides a promising approach to navigating the heterogeneity of autism spectrum conditions. The current study investigated sensory processing in individuals with a rare genetic event that is highly penetrant for autism, 16p11.2 deletions, using a well-characterized visual paradigm, binocular rivalry, which is thought to be a non-invasive index of excitatory/inhibitory balance in the visual cortex. We characterized rivalr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
0
3
1
Order By: Relevance
“…Similarly, it has been hypothesized that the perceptual alternations in binocular rivalry are, at least in part, the result of modulation by right‐sided fronto‐parietal brain regions in attention network (Lumer et al, 1998; Tong et al, 2006). In autism, it has been consistently found that the rate of transitions in binocular rivalry is slower (Choi et al, 2023; Freyberg et al, 2015; Robertson et al, 2013; Spiegel et al, 2019), however our current results show that spatial attention sampling rate is not changed. Future work is needed to clarify the relationship between attentional oscillations and binocular rivalry and their underlying cortical dynamics, and how these mechanisms may differ and interact in autism.…”
Section: Discussioncontrasting
confidence: 65%
“…Similarly, it has been hypothesized that the perceptual alternations in binocular rivalry are, at least in part, the result of modulation by right‐sided fronto‐parietal brain regions in attention network (Lumer et al, 1998; Tong et al, 2006). In autism, it has been consistently found that the rate of transitions in binocular rivalry is slower (Choi et al, 2023; Freyberg et al, 2015; Robertson et al, 2013; Spiegel et al, 2019), however our current results show that spatial attention sampling rate is not changed. Future work is needed to clarify the relationship between attentional oscillations and binocular rivalry and their underlying cortical dynamics, and how these mechanisms may differ and interact in autism.…”
Section: Discussioncontrasting
confidence: 65%
“…The term was first introduced to explain sensory, social, and emotional behaviors in individuals with ASD [ 265 ]. Binocular rivalry is a perceptual process that emphasizes the importance of reciprocal inhibition [ 266 , 267 ], which is dependent on E/I dynamics and is reduced in individuals with ASD [ 268 , 269 ]. The distribution of neurons in the neocortex is arranged in mini-columns, which modulates the microcircuitry of glutamatergic and GABAergic signaling.…”
Section: Vpa and Disruption Of Brain Developmentmentioning
confidence: 99%
“…Given the potential for improvement when therapy is started at an early age (Bernier et al 2017), evaluation by age 3 is recommended despite traditional recommendations to wait until age 7 to assess for auditory processing difficulties. • Evaluation for visual processing disorders (Choi et al 2023) is recommended (Kooiker et al 2020) by age 4 with an experienced developmental optometrist and subsequent vision therapy if necessary. • Brain MRI to assess for Chiari malformation if there are recurring headaches (Schaaf et al 2011).…”
Section: Anticipatory Guidance From 1 Month To 1 Yearmentioning
confidence: 99%
“…• Educationally based mental health services assessment should be completed between the ages of 5-7 and reassessed as part of the IEP. • Evaluation for auditory and visual processing disorder if not done already and under continued specialty care (Jenkins et al 2016), (Choi et al 2023).…”
Section: Health Supervision From 5 To 12 Years: Late Childhoodmentioning
confidence: 99%